Smart Dispenser Menggunakan Voice Recognition Berbasis Mikrokontroler - Antony Richardo; Dodon Yendri (CHIPSET, 2022)
Voice recognition technology is one of the technological breakthroughs that is currently widely used. The operation of voice recognition is only by saying commands to control devices that are integrated with the user as a tool to facilitate human activities and even replace the role of humans in certain functions. In using the dispenser, it is necessary to choose cold or hot water and pull the faucet directly on the dispenser, while during a pandemic like today, we are required to reduce direct contact with objects that are used together. The use of the dispenser also has limitations for the amount of water released because it cannot be measured in a definite amount because there has been no research conducted to regulate the amount of water that is filled into the glass used by the user. For this reason, the use of the Voice Recognition module can be used as a solution to reduce direct touch to the dispenser because it utilizes voice commands given by the user and the Waterflow sensor is used to calculate the amount of water that will come out of the water faucet on the dispenser.